E-Cigarettes and Vaping. (June 2020) - Hammond, Stephanie; Phillips, Jennan
Once considered a harmless alternative to smoking tobacco, e-cigarettes are now a public health threat. Occupational health nurses should recommend workers avoid using e-cigarettes and vaping unless suggested by their doctor for smoking cessation purposes.